IS INFLATION A PURELY MONETARY PHENOMENON? EMPIRICAL INVESTIGATION FROM NIGERIA. (1970 –2009) - Adenuga, Idris Abiodun; Bello, Hassan Taiwo; Ejumedia, Patrick Efe (European Scientific Journal, ESJ, 2012)
This paper examines weather inflation is purely a monetary phenomenon in Nigeria using annual data from 1970-2009, the econometric approaches adopted in the paper is the Ordinary least square (OLS). This study comes out with empirical evidence that will help in understanding the causes of inflation in Nigeria. The study concludes that inflation is not a purely monetary phenomenon in Nigeria as the coefficient of broad money supply is less than unity. However, the variable is highly significant in explaining inflation in Nigeria. The result indicates that the regressors in the model are highly significant in causing inflation in Nigeria as shown by the F-statistic.